2011
DOI: 10.3389/fmicb.2011.00027
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with human induced pluripotent stem cells creates an antigen-specific immune response against HIV-1 gp160

Abstract: Induced pluripotent stem cells (iPSCs) are artificially derived from somatic cells that have been transduced with defined reprogramming factors. A previous report has indicated the possibility of using iPSCs as an immune stimulator to generate antigen-specific immunity. In our current study, we have investigated whether human iPSCs (hiPSCs) have the ability to enhance specific immune response against a human immunodeficiency virus type 1 (HIV-1) antigen in a xenogenic mouse model. Our results show that BALB/c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Our RNA‐sequencing results showed that cancer cells and ESCs/iPSCs share several tumor‐associated antigens. iPSC‐based vaccines can induce antitumor immunity [7, 35–37]. Autologous iPSCs can provide more accurate and representative tumor‐related antigens [38], thus opening up new possibilities [14, 39, 40].…”
Section: Discussionmentioning
confidence: 99%
“…Our RNA‐sequencing results showed that cancer cells and ESCs/iPSCs share several tumor‐associated antigens. iPSC‐based vaccines can induce antitumor immunity [7, 35–37]. Autologous iPSCs can provide more accurate and representative tumor‐related antigens [38], thus opening up new possibilities [14, 39, 40].…”
Section: Discussionmentioning
confidence: 99%